2017
DOI: 10.1021/acs.orglett.7b01724
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Energy and π-Conjugation Effects on Photoisomerization of Chiral N,C-Chelate Organoborons with PAH Substituents

Abstract: Chiral, PAH substituted N,C-chelate boron compounds are systematically investigated to establish the effect of triplet energy and substitution position on their photoreactivity. They all undergo regioselective photoisomerization, forming new dark isomers with quantum efficiencies reflecting these various factors. New PAH fused 4bH-azaborepins are obtained via thermal isomerization of the dark isomers. These results further implicate a photoactive triplet state in the photoisomerization process and its utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Owing to the concomitant formation of two photoproducts, the quantum yields of isomerization could not be determined. The importance of the proximity of the boron center and the C2−S bond in 1 / 1 a and 2 / 2 a was confirmed by the photoreaction of 1′ (Scheme ), which follows that of A → C in Scheme ,. Therefore, the C2−B connectivity in 1 / 1 a and 2 / 2 a plays a critical role in facilitating the photogeneration of 1 b and 2 b , which is elucidated in the computed reaction pathway for 1 to 1 b .…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…Owing to the concomitant formation of two photoproducts, the quantum yields of isomerization could not be determined. The importance of the proximity of the boron center and the C2−S bond in 1 / 1 a and 2 / 2 a was confirmed by the photoreaction of 1′ (Scheme ), which follows that of A → C in Scheme ,. Therefore, the C2−B connectivity in 1 / 1 a and 2 / 2 a plays a critical role in facilitating the photogeneration of 1 b and 2 b , which is elucidated in the computed reaction pathway for 1 to 1 b .…”
Section: Methodsmentioning
confidence: 74%
“…This approach has several advantages, with the most prominent being the ability to access reactive intermediates from easily prepared and often air‐stable starting materials. Using this approach, we have recently unveiled a number of photoinitiated transformations available to N,C‐chelate boron compounds (e.g., A ; Scheme ), wherein readily accessible precursors were converted into novel B,N‐embedded systems such as azaboratabisnorcaradienes ( B ),, B,N‐1,4,6‐cyclooctatrienes, azaborabenzotropilidenes, and 4b H ‐azaborepins ( C ),, which all display interesting properties and would be very difficult to prepare by traditional synthetic procedures. In many of these examples, the photogenerated boriranes B act as reactive intermediates, enabling subsequent transformations to more stable isomers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four-coordinate triarylboranes with three different substituents are interesting molecules, 7 , 18 yet their syntheses are very rare due to the great challenge of selectivity. How to realize their construction in a one pot strategy has become a very attractive challenge.…”
Section: Resultsmentioning
confidence: 99%
“…However, isolated and well-characterized DHPs are rarely reported in the literature . Photoisomerization of boranes and their derivatives has emerged as a promising way to generate rare boron-doped polycyclic structures. , Studies of borylated stilbenes have also been reported. , For example, Shi et al recently found that stilbene analogues containing a para -substituted donor–acceptor (D–A; Mes 2 B–Ph– p -NMe 2 ) unit can produce rather rare but stable 4a,4b-DHP intermediates (Scheme b) . To better understand the effect of the donor and/or acceptor on the photoreactivity of the stilbene analogues, we decided to synthesize Mes 2 B-functionalized stilbene derivatives with varying aryl substituents, as shown in Scheme c.…”
mentioning
confidence: 99%